International organisations and the role of collective bargaining. (May 2019) - Pedersini, Roberto
This article analyses the positions on the role of collective bargaining of international organisations dealing with economic and employment issues. A stylised framework is developed that looks at each international organisation's mission, expert knowledge and structure (at political and technical levels). The analysis concludes that most of the international organisations under review remain anchored to their missions and mainstream economic analyses, with the exception of the OECD (partially) and the ILO. In contrast, the European Commission has a quite different nature, being part of a fully-fledged polity. The article concludes that the more nuanced position on the role of collective bargaining emerging from international organisations includes some important elements. In particular, the recognition of its potential for social inclusion and cohesion may support national measures that promote collective bargaining.